Table tennis players use superior saccadic eye movements to track moving visual targets - Nakazato, Riku; Aoyama, Chisa; Komiyama, Takaaki; Himo, Ryoto; Shimegi, Satoshi (Frontiers in Sports and Active Living, 2024)
Introduction: Table tennis players perform visually guided visuomotor responses countlessly. The exposure of the visual system to frequent and long-term motion stimulation has been known to improve perceptual motion detection and discrimination abilities as a learning effect specific to that stimulus, so may also improve visuo-oculomotor performance. We hypothesized and verified that table tennis players have good spatial accuracy of saccades to moving targets. Methods: University table tennis players (TT group) and control participants with no striking-sports experience (Control group) wore a virtual reality headset and performed two ball-tracking tasks to track moving and stationary targets in virtual reality. The ball moved from a predetermined position on the opponent's court toward the participant's court. 54 conditions were examined for the moving targets in combinations of 3 ball trajectories (familiar parabolic, unfamiliar descent, and unfamiliar horizontal), 3 courses (left, right, and center), and 6 speeds. Results: All participants primarily used catch-up saccades to track the moving ball. The TT group had lower mean and inter-trial variability in saccade endpoint error compared to the Control group, showing higher spatial accuracy and precision, respectively. The superiority of the spatial accuracy in the TT group was seen in both the right and the left courses for all trajectories but that of precision was for familiar parabolic only. There was no difference between the two groups in the onset time or spatial accuracy of saccades for stationary targets appearing at various positions on the ping-pong table. Discussion: Table tennis players had high ability and stability to saccade to moving targets accurately, suggesting their improvement of the ability to analyze the direction and speed of the ball's movement and predict its trajectory and future destination. The trajectory dependence of improved saccade precision in the TT group implies the possibility that the motion vision system was trained by the visual stimuli frequently encountered in table tennis. tennis players can obtain high performance (spatial accuracy and precision) of saccades to track moving targets as a result of motion vision ability improved through a vast amount of visual and visuo-ocular experience in their play.